2018
DOI: 10.12973/iji.2018.11439a
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence Enhancement Impacts on Developing Speaking Skill among EFL Learners: an Empirical Study

Abstract: Affective factors play a role in learning in general and language learning in particular. The current study tried to empirically examine the influence of one of these factors namely 'Emotional Intelligence' to check its influence on Speaking Skill. Participants were Intermediate level students who took the IELTS test (International English Language Testing System), so that the researchers could evaluate their proficiency in speaking skill at the beginning of the project. Next, the Emotional Intelligence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
(16 reference statements)
2
11
0
Order By: Relevance
“…Based on in table 2 (test of kruskal wallis), it was found that the students who have a high level of emotional intelligence have better speaking skills than those who have a low level of emotional intelligence. The results of this study in accordance with the research of Ebrahimi, Khoshsima, & Behtash (2008) who explained that the emotional intelligence is the ability to improve thinking and understanding of interpersonal dynamics through the amalgamation of intelligence, empathy, and emotion. In addition, the study results were also relevant to the study conducted by Bora (2012), about the impact of emotional intelligence on the development of speaking skills: from a brainbased perspective.…”
Section: Table 2 Test Of Kruskal Wallissupporting
confidence: 91%
See 1 more Smart Citation
“…Based on in table 2 (test of kruskal wallis), it was found that the students who have a high level of emotional intelligence have better speaking skills than those who have a low level of emotional intelligence. The results of this study in accordance with the research of Ebrahimi, Khoshsima, & Behtash (2008) who explained that the emotional intelligence is the ability to improve thinking and understanding of interpersonal dynamics through the amalgamation of intelligence, empathy, and emotion. In addition, the study results were also relevant to the study conducted by Bora (2012), about the impact of emotional intelligence on the development of speaking skills: from a brainbased perspective.…”
Section: Table 2 Test Of Kruskal Wallissupporting
confidence: 91%
“…The Trait of emotional intelligence questionnaire (TEIQue) is organized under four factors, namely: well-being, self-control, emotionality, and sociability and the component of emotional intelligence such as emotional self-awaress (Genc, Kulusakh, & Aydin, 2016). Afshar and Rahimi conducted the investigation of the relationship between critical thinking, emotional intelligence, and speaking abilities of Iranian EFL learners (Ebrahimi, Khoshsima, & Behtash, 2008). The students filled out the questionnaire of Bar-On emotional intelligence that took the California Critical Thinking Skills Test (CCTST) form B, and had an interview.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the model of triadic reciprocity proposed in this study explains the correlational The previous studies determined the connection between EI and oral communication skills in various fields. For instance, several researchers determined the relationship between two variables in the academic fields of business, English language and science (Afshar, & Rahimi, 2014;Chang & Hu, 2017;Ebrahimi, Khoshsima, Zare-Behtash, & Heydarnejad, 2018;Fall, Kelly, MacDonald, Primm, & Holmes, 2013;Schutte et al, 2002). All of these studies revealed a substantial connection between EI and oral communication skills.…”
Section: Research Objectivesmentioning
confidence: 99%
“…Their findings showed that learners' high motivation resulted in a high level of confidence, and, consequently a positive attitude towards using writing strategies. Besides, emotional intelligence enhancement influences on developing speaking skill in EFL learning settings were examined by Ebrahimi, Khoshsima, Zare Behtash, and Heydarnejad (2018). Based on this research, significant improvement in speaking is achieved by considering the role of emotional intelligence in improving speaking ability.…”
Section: Emotions and Teaching Productive Skillsmentioning
confidence: 99%